Bacterial concrete: A review on self-healing properties in the light of sustainability. (2022) - Khaudiyal, Shreya; Rawat, Anurag; Das, Sourav Kumar; Garg, Nikhil
Abstract: Concrete is perhaps the only indispensable material in the industry today. The comparatively high durability and compressive strength and the ability to easily work with gives it an edge over other building materials making it suitable for industrial as well as domestic work. With all its advantages, concrete still battles with many issues. It is not a hidden fact that the concrete is comparatively weak in tension due to which a lot of durability issues arise. Various physiological and environment factors can generate irrevocable damage to the structure which further affect the structural durability and eventually develop cracks and micro-cavity in the structure. The crack formation is not good for structural health. There are plenty of conventional methods to fill in the cracks and remediate structure damage, but most of these methods are tedious, expensive and/or hazardous to environment. This led to the pursuit of an effective and healthy remediation technique which would be effectively filling up cracks without deteriorating our environment and the concept of bacterial concrete fill in the description just right. The method of biomineralization or simply bacterial concrete method is a process where calcite precipitating bacteria are incorporated into the concrete in certain proportions which served as a great self-healing innovation in the industry. The bacteria when encountered water, precipitated calcium carbonate thereby healing cracks. This self-healing technique displayed efficient monitoring of structural health, detects damage, and expeditiously filled in the gap. The method is not only safe from the environment point of view but provides extra durability and longevity to the structure. This study aims to investigate about the self-healing capacity and the mechanism involved in the process. It covers the studies and experiments carried out so far in this field and compares the fresh and hardened properties of bacterial concrete with the normal concrete mix. The study also discusses the potential capacity of the method, and an average optimum dosage value is also suggested based on the prior experiments done by researchers so far.